Aromatic naphthenic acids in oil sands process-affected water, resolved by GCxGC-MS, only weakly induce the gene for vitellogenin production in zebrafish (danio rerio) larvae - Reinardy, H.; Scarlett, Alan; Henry, T.; West, C.; Hewitt, L.; Frank, R.; Rowland, S. (2013)
Process waters from oil sands industries (OSPW) have been reported to exhibit estrogenic effects. Although the compounds responsible are unknown, some aromatic naphthenic acids (NA) have been implicated. The present study was designed to investigate whether aromatic NA might cause such effects. Here we demonstrate induction of vitellogenin genes (vtg) in fish, which is a common bioassay used to indicate effects consistent with exposure to exogenous estrogens. Solutions in water of 20-2000 µg L-1 of an extract of a total OSPW NA concentrate did not induce expression of vtg in larval zebrafish, consistent with earlier studies which showed that much higher NA concentrations of undiluted OSPW were needed. Although 20-2000 µg L-1 of an esterifiable NA subfraction of the OSPW NA concentrate did induce expression, this was of much lower magnitude to that induced by much lower concentrations of 17a-ethynyl estradiol, indicating that the effect of the total NAs was only weak. However, given the high NA concentrations and large volumes of OSPW extant in Canada, it is important to ascertain which of these esterifiable NA in the OSPW produce the effect. Up to 1000 µg L-1 of an OSPW subfraction containing only alicyclic NA, and considered by most authors to be NA sensu stricto, did not produce induction; but, as predicted, 10-1000 µg L-1 of an aromatic NA fraction did. Such effects by the aromatic acids are again consistent with those of only a weak estrogenic substance. These findings may help to focus studies of the most environmentally significant OSPW-related pollutants, if reproduced in a greater range of OSPW. © 2013 American Chemical Society.